2014
DOI: 10.1016/j.cardfail.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Skeletal Muscle Gene Expression Patterns and the Impact of Functional Capacity in Patients With Systolic Heart Failure

Abstract: Background Declining physical function is common among systolic heart failure (HF) patients and heralds poor clinical outcomes. We hypothesized that coordinated shifts in expression of ubiquitin-mediated atrophy-promoting genes are associated with muscle atrophy and contribute to decreased physical function. Methods Systolic HF patients (left ventricular ejection fraction [LVEF] ≤40%) underwent skeletal muscle biopsies (nondominant vastus lateralis) and comprehensive physical assessments. Skeletal muscle gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
2
12
1
Order By: Relevance
“…However, the transcript level of Foxo1, but not those of MAFbx and MuRF‐1, is elevated in the vastus lateralis muscle of patients with systolic heart failure (Forman et al . ). Intriguingly, the results of the present study showed that a concomitant increase of acetylated Foxo1 and MuRF‐1 induced by doxorubicin treatment was observed only in the hearts of young but not aged mice.…”
Section: Discussionmentioning
confidence: 97%
“…However, the transcript level of Foxo1, but not those of MAFbx and MuRF‐1, is elevated in the vastus lateralis muscle of patients with systolic heart failure (Forman et al . ). Intriguingly, the results of the present study showed that a concomitant increase of acetylated Foxo1 and MuRF‐1 induced by doxorubicin treatment was observed only in the hearts of young but not aged mice.…”
Section: Discussionmentioning
confidence: 97%
“…The UPS has been shown to act in a number of cachectic conditions, with an upregulation of proteins involved in the proteasome pathway such as polyubiquitins, Ub fusion proteins, the Ub ligases MAFbx, and MuRF‐1, detected in animal models of diabetes mellitus, uremia, and also cancer . However, whether the UPS plays a central role in HF seems less clear, as some but not all patient studies have found muscle biopsies to have an increased MuRF‐1 and MAFbx expression. That a coronary artery ligation model of HF in rats has also shown muscle wasting and higher proteasome activity in the plantaris and soleus, reinforces the importance of the UPS in cardiac cachexia.…”
Section: Molecular Mechanisms Of Cachexiamentioning
confidence: 99%
“…In patients with HFpEF, as well as in patients with systolic cardiac dysfunction, the degree of exercise intolerance is not directly related to the degree of cardiac weakness but somewhat surprisingly, the symptoms of dyspnea and fatigue in HF or often directly related to abnormalities of skeletal musculature in HF, 101 which has been reviewed in detail elsewhere. 102 …”
Section: Mechanisms Of Et Benefits In Hfmentioning
confidence: 99%